Polymorphisms of Gene Cassette Promoters of the Class 1 Integron in Clinical Proteus Isolates - Xiao, Linlin (Front Microbiol, 2019)
OBJECTIVE: To describe the polymorphisms of gene cassette promoters of the class 1 integron in clinical Proteus isolates and their relationship with antibiotic resistance. METHODS: Polymorphisms of the gene cassette promoter in 153 strains of Proteus were analyzed by PCR and nucleotide sequencing. Variable regions of atypical class 1 integrons were detected by inverse PCR and nucleotide sequencing. Enterobacterial repetitive intergenic consensus (ERIC)-PCR was used to analyze the phylogenetic relationships of class 1 integron-positive clinical Proteus isolates. Representative beta-lactamase genes (bla), including bla(TEM),bla(SHV),bla(CTX-M-1),bla(CTX-M-2),bla(CTX-M-8),bla(CTX-M-9),bla(CTX-M-25) and bla(OXA-1), and plasmid-mediated quinolone resistance (PMQR) genes including qnrA, qnrB, qnrC, qnrD, qnrS, oqxA, oqxB, qepA, and aac(6′)-Ib were also screened using PCR and sequence analysis. RESULTS: Fifteen different gene cassette arrays and 20 different gene cassettes were detected in integron-positive strains. Of them, aadB-aadA2 (37/96) was the most common gene cassette array. Two of these gene cassette arrays (estX-psp-aadA2-cmlA1, estX-psp-aadA2-cmlA1-aadA1a-qacI-tnpA-sul3) have not previously been reported. Three different Pc-P2 variants (PcS, PcW(TGN-10), PcH1) were detected among the 96 Proteus strains, with PcH1 being the most common (49/96). Strains carrying the promoters PcS or PcW(TGN-10) were more resistant to sulfamethoxazole, gentamicin and tobramycin than those carrying PcH1. Strains with weak promoter (PcH1) harbored significantly more intra- and extra-integron antibiotic resistance genes than isolates with strong promoter (PcW(TGN-10)). Further, among 153 isolates, representative beta-lactamase genes were detected in 70 isolates (bla(TEM-1), 54; bla(OXA-1), 40; bla(CTX-M-3), 12; bla(CTX-M-14), 12; bla(CTX-M-65), 5; bla(CTX-M-15), 2) and representative PMQR genes were detected in 87 isolates (qnrA, 6; qnrB, 3; qnrC, 5; qnrD, 46; qnrS, 5; oqxA, 7; aac(6′)-Ib, 13; aac(6′)-Ib-cr, 32). CONCLUSION: To the best of our knowledge, this study provides the first evidence for polymorphisms of the class 1 integron variable promoter in clinical Proteus isolates, which generally contain relatively strong promoters. Resistance genotypes showed a higher coincidence rate with the drug-resistant phenotype in strong-promoter-containing strains, resulting in an ability to confer strong resistance to antibiotics among host bacteria and a relatively limited ability to capture gene cassettes. Moreover, strains with relatively weak integron promoters can “afford” a heavier “extra-integron antibiotic resistance gene load”. Furthermore, the gene cassettes estX, psp and the gene cassette arrays estX-psp-aadA2-cmlA1, estX-psp-aadA2-cmlA1-aadA1a-qacI-tnpA-sul3 have been confirmed for the first time in clinical Proteus isolates. Beta-lactamase genes and PMQR were investigated, and bla(TEM-1) and bla(OXA-1) were the most common, with qnrD and aac (6′)-Ib-cr also being dominant.